O crime de lesa-majestade no caso da inconfidência mineira: tipificação, fontes do direito e silêncio infiel - Farias, Delmiro Ximenes de (2019)
For the crimen laesae maiestatis, most known as high treason, the participants in the Inconfidência Mineira were convicted in 1792. They were a group of wealthy members of the community in Minas Gerais captaincy who desired the independence for the region, with a separation from Portugal. The main regulation of the state at the time about that crime was the book V from the Ordenações Filipinas. However, the legal practice was more inclined to common law than to state law. Common law was a complex of statutes and teachings about roman, canonic and germanic law, that emerged in the middle ages, and had a great importance during the Ancien Régime. Thus, the subsidiary law, which included the ius commune, and should be applied only in case of gaps in the portuguese legal order, had more influence than the formal legislation. In 1769, appear the so called Lei da Boa Razão which intended to centralize the power in the hands of the king, through restrictions using the subsidiary law. In this context, the crimen laesae maiestatis was formed not only by the state law, but also by other sources of law. Generally, the crime occurred when a subject’s behavior challenged the power of the prince or when brought danger to the state. The crime sought to protect the maiestas, the state’s organization and the status quo. This paper intends to better understand the typification and the tipicality of the Inconfidência Mineira as a crimen laesae maiestatis, both in relation to those who had active participation in the uprising, as well as those who only knew about the conspiracy, but did not report to the authorities. In addition, it is necessary know: how the portuguese history led to the Inconfidência; the main sources of law in Portugal; understand in abstract the details about the crime, its foundations, species, and its treatment by common law and portuguese law. The idea of typification and tipicality at the time relegate the legality principle that we have in contemporary criminal law. The typification and typicality occurred not only based on statutes, but also in the subsidiary law. Analyzing the behavior of the inconfidentes, some of them incurred in the item 5, title VI, and book V, from Ordenações Filipinas. However, those who were convicted for merely did not report the Inconfidência to the authorities do not fit in that provision. There was a legal gap to be resolved by the subsidiary law, by a non-statute source. Examining these sources, it can be seen that the unfaithful silence can be considered crime, regardless its purpose of helping or not the sedition. To arrive to such conclusion, works about the Inconfidência Mineira was used, including the devassas documents, as well the literature regarding the crimen laesae maiestatis, portuguese legislation, and the Corpus Iuris Civilis.